Relationship of Retinal Zone and Plus Severity with the Requirement of Re-Treatment in Bevacizumab-Treated Eyes for Retinopathy of Prematurity - Sadik Etka Bayramoglu; Nihat Sayin; Ibrahim Kocak (Ophthalmic Research)
Introduction: The aim of this study was to investigate the relationship between the location of retinal vascularization and plus severity with re-treatment rates in intravitreal bevacizumab (IVB)-treated eyes. Methods: For this retrospective, observational study, 200 eyes treated with IVB for type 1 retinopathy of prematurity (ROP) and aggressive-ROP were included. The pretreatment retinal vascularization was evaluated by analyzing quantitative measurements of optic disc-to-fovea distance (DFD), disc diameter, and shortest and longest distance between the optic disc and ridge of wide-field fundus photographs (WFPs). Plus severity was qualified in five grades such as normal, pre-plus, mild plus, moderate plus, and severe plus by evaluating WFPs. Re-treatments up to 60 weeks of postmenstrual age (PMA) were evaluated. Re-treated eyes up to first month after initial treatment were labeled as early re-treatment group and re-treated eyes after the first month of initial treatment up to 60 weeks of PMA were labeled as middle-term re-treated group. Results: Thirty-six percentage of eyes had zone I, 64% of eyes had zone II disease, and 42% eyes had mild plus disease. Forty-three (21.5%) eyes of 23 infants underwent re-treatment prior to 60 weeks of PMA. Thirteen eyes and 30 eyes were in the early- and middle-term re-treated groups, respectively. In middle-term re-treated group, 27 (13.5%) eyes re-treated for progressive reactivated disease, and 3 (1.5%) eyes re-treated for prophylactic purposes. Advanced pretreatment retinal vascularization and high birth weight were negatively associated with the re-treatment rate (p = 0.016, odds ratio = 0.774; p = 0.041, odds ratio = 0.999, respectively). There was a positive association between the re-treatment rate and pretreatment plus severity (p = 0.044, odds ratio = 1.449). The lower ratio of shortest distance between the optic disc and ridge to DFD was considered as an independent predictive variable for higher rate of re-treatment (p = 0.002; odds ratio: 0.450). Conclusion: The location of retinal vascularization and plus disease showed a wide distribution in bevacizumab-treated eyes. Graded evaluation of retinal vascularization and plus severity may help predict the need for additional treatment. Unresponsiveness to the initial treatment, increased fibrotic activity, progressive reactivated stage 2–3 ROP, extraretinal new vessels, and prophylactic purposes were the main re-treatment indications.